Task-induced deactivation dysfunction during reward processing is associated with low self-esteem in a possible subtype of major depression - Jüllig, Antonia; Hebib, Sandi; Metzker, Helena; Gruber, Eva Stefanie; Gruber, Oliver (Brain and behavior, 2024)
Introduction Low self-esteem is a frequent symptom in major depressive disorder (MDD). This functional magnetic resonance imaging study investigated whether MDD patients with low self-esteem show a distinct neural pathophysiology. Previous studies linked low self-esteem to reduced task-induced deactivation of the pregenual anterior cingulate cortex (pgACC) as a part of the default mode network, and to reduced connectivity between pgACC and reward system. Goya-Maldonado et al. identified an MDD subtype with pgACC and ventral striatal overactivations during reward processing. We hypothesized that this subtype might be characterized by low self-esteem. Methods Eighty-three MDD patients performed the desire-reason dilemma task and completed the Rosenberg Self-Esteem Scale (RSES). Brain activity during bottom-up reward processing was regressed upon the RSES scores, controlling for depression severity measured by the Montgomery-Åsberg Depression Rating Scale. To corroborate the findings, we compared self-esteem scores between patient subgroups with impaired task-induced deactivation (n = 31) and with preserved task-induced deactivation (n = 31) of the pgACC. Results Consistent with our a priori hypothesis, activity in a bilateral fronto-striatal network including pgACC and ventral striatum correlated negatively with RSES scores, also when controlling for depression severity. In the additional analysis, patients with impaired task-induced pgACC deactivation showed lower self-esteem (t (52.82) = −2.27; p = .027, d = 0.58) compared to those with preserved task-induced pgACC deactivation. Conclusions We conclude that low self-esteem in MDD patients is linked to a task-induced deactivation dysfunction of the pgACC. Our findings suggest that a previously described possible subtype of MDD with pgACC and ventral striatal overactivations during reward processing is clinically characterized by low self-esteem.
Zuerst veröffentlicht: 14. Juni 2024
Gesehen am 15.11.2024